Improving Clinical Manufacturing of IL-15 Activated Cytokine-Induced Killer (CIK) Cells - Bremm, Melanie; Pfeffermann, Lisa-Marie; Cappel, Claudia; Katzki, Verena; Erben, Stephanie; Betz, Sibille; Quaiser, Andrea; Merker, Michael; Bonig, Halvard; Schmidt, Michael; Klingebiel, Thomas; Bader, Peter; et al. (Frontiers in Immunology, 2019)
Cytokine-induced killer (CIK) cells are an immunotherapeutic approach to combat relapse following allogeneic hematopoietic stem cell transplantation (HSCT) in acute leukemia or myelodysplastic syndrome (MDS) patients. Prompt and sequential administration of escalating cell doses improves the efficacy of CIK cell therapy without exacerbating graft versus host disease (GVHD). This study addresses manufacturing-related issues and aimed to develop a time-, personal- and cost-saving good manufacturing process (GMP)-compliant protocol for the generation of ready-for-use therapeutic CIK cell doses starting from one unstimulated donor-derived peripheral blood (PB) or leukocytapheresis (LP) products. Culture medium with or without the addition of either AB serum, fresh frozen plasma (FFP) or platelet lysate (PL) was used for culture. Fresh and cryopreserved CIK cells were compared regarding expansion rate, viability, phenotype, and ability to inhibit leukemia growth. Cell numbers increased by a median factor of 10-fold in the presence of FFP, PL or AB serum, whereas cultivation in FFP/PL-free or AB serum-free medium failed to promote adequate CIK cell proliferation (p<0.01) needed to provide clinical doses of 1x106 T cells/kG, 5x106 T cells/kG, 1x107 T cells/kG, and 1x108 T cells/kG recipient body weight. CIK cells consisting of T cells, T- natural killer (T-NK) cells and a minor fraction of NK cells were not significantly modified by different medium supplements. Moreover, neither cytotoxic potential against leukemic THP-1 cells nor cell activation shown by CD25 expression were significantly influenced. Moreover, overnight and long-term cryopreservation had no significant effect on the composition of CIK cells, their phenotype or cytotoxic potential. A viability of almost 93% (range: 89 - 96) and 89.3% (range: 84 – 94) was obtained after freeze-thawing procedure and long-term storage, respectively, whereas viability was 96% (range: 90 – 97) in fresh CIK cells. Altogether, GMP-complaint CIK cell generation from an unstimulated donor-derived PB or LP products was feasible. Introducing FFP, which is easily accessible, into CIK cell cultures was time- and cost-saving without loss of viability and potency in a 10-12 day batch culture. The feasibility of cryopreservation enabled storage and delivery of sequential highly effective ready-for-use CIK cell doses and therefore reduced the number of manufacturing cycles.